The dialectical relationship between African cultures and child marriages as portrayed by the herald and newsday - Shiri, Ruvimbo F. (Midlands State University, 2018)
Child marriages are a form of abuse and a violation of children’s rights. The media are found at the core of this study as it questions the media’s watchdog character. The purpose of the study was to find out the role played by The Herald and Newsday in their child marriage reportage, assess how African cultures have perpetuated the practice of child marriages and lastly to discover the intervention strategies that have been put in place to address the situation. The research made use of various scholars who conducted different studies so as to understand the issue in the Zimbabwean setup. To better understand child marriages and its portrayal by The Herald and Newsday, the researcher made use of two conceptual frameworks that is framing and hegemony. For data collection, the research utilised archival research, interviews and questionnaires. A thematic approach was applied in presenting and analysing the content acquired from data collection. As portrayed in the two newspapers under study, child marriages were not given much prominence and salience. The research proved that information published on child marriages was acquired from partner organisations and this depicts lack of depth in such stories. It also proved that cultural practices influence child marriages as represented in early marriage articles. The research recommends that The Herald and Newsday put children matters such as their rights, in the public agenda so that children’s voices are heard. It also recommends Save the Children to continue lobbying policies so that children are well protected by the media, government and society at large. Save the Children is one of the organisations that advocates for children’s rights in Zimbabwe. It also highlighted areas that can be taken up for further studies.